Penggunaan Media Gambar Langkah Kaki Terhadap Hasil Belajar Pencak Silat Seni Tepak Tilu Jalan Muka Satu - Rahmawati, Ahti; Rohman, Oom; Sucipto, Sucipto (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2023)
Abstract Learning media has a big enough role in efforts to improve learning outcomes. Pencak silat is one of the sports that is studied in schools as part of efforts to preserve national culture, however, learning pencak silat is often learning material that is considered old-fashioned and boring and movements that are quite difficult for students because the movements must be memorized in pencak silat. silat is quite diverse, especially in the category of ibing martial arts, so that it has an impact on learning outcomes. The purpose of this study was to determine the implementation of media images of footsteps on the learning outcomes of the pencak silat art of tap tilu one way street in high school students. This study uses the experimental method, the research design used in this study is the Posttest Only Control Design. The research sample was class X high school students with a total of 30 people. The research instrument uses the standard assessment of the national jury referee in the ibing category. Based on the research results obtained (1) the learning outcomes using the normality test show that the value (L count) in the post-test of the two classes is smaller than the table value with degrees of freedom (α = 0.05). This means that the variances of the two samples are the same or homogeneous. (2) Then the calculation of the t-test in table 4.5 obtained a significance value at the time of the posttest, a significance value of 2.36 ˃ 1.753 was obtained, then H0 was rejected, meaning that there was a significant difference in the effect of learning outcomes between the experimental group and the control group, it can be explained that the implementation of media images of footsteps has a significant influence on the learning outcomes of pencak silat, the art of tepak tilu, one way face for students in senior high schools.. Keywords: images, footsteps, learning outcomes, martial arts, tepak tilu.